BATIK TRAINING ON NURSING HOUSE âWANITA UTAMAâ SURAKARTA - Riani, Asri Laksmi; Handayani, Sarah Rum; Rahmawati, Rahmawati (Universitas Muhammadiyah Surakarta, 2011)
The purpose of this study is to be able to guide and direct the prostitutes (WTS) in Surakarta and itâs surrounding environment on the nursing house